First-line nivolumab plus chemotherapy versus chemotherapy alone for advanced gastric, gastro-oesophageal junction, and oesophageal adenocarcinoma (CheckMate 649): a randomised, open-label, phase 3 trial. Issue 10294 (3rd July 2021) - Janjigian, Yelena Y; Shitara, Kohei; Moehler, Markus; Garrido, Marcelo; Salman, Pamela; Shen, Lin; Wyrwicz, Lucjan; Yamaguchi, Kensei; Skoczylas, Tomasz; Campos Bragagnoli, Arinilda; Liu, Tianshu; Schenker, Michael; et al.
Summary: Background: First-line chemotherapy for advanced or metastatic human epidermal growth factor receptor 2 (HER2)-negative gastric or gastro-oesophageal junction adenocarcinoma has a median overall survival (OS) of less than 1 year. We aimed to evaluate first-line programmed cell death (PD)-1 inhibitor-based therapies in gastric, gastro-oesophageal junction, and oesophageal adenocarcinoma. We report the first results for nivolumab plus chemotherapy versus chemotherapy alone. Methods: In this multicentre, randomised, open-label, phase 3 trial (CheckMate 649), we enrolled adults (≥18 years) with previously untreated, unresectable, non-HER2-positive gastric, gastro-oesophageal junction, or oesophageal adenocarcinoma, regardless of PD-ligand 1 (PD-L1) expression from 175 hospitals and cancer centres in 29 countries. Patients were randomly assigned (1:1:1 while all three groups were open) via interactive web response technology (block sizes of six) to nivolumab (360 mg every 3 weeks or 240 mg every 2 weeks) plus chemotherapy (capecitabine and oxaliplatin every 3 weeks or leucovorin, fluorouracil, and oxaliplatin every 2 weeks), nivolumab plus ipilimumab, or chemotherapy alone. Primary endpoints for nivolumab plus chemotherapy versus chemotherapy alone were OS or progression-free survival (PFS) by blinded independent central review, in patients whose tumours had a PD-L1 combined positive score (CPS) of five or more. Safety was assessed in all patients who received at least one dose of the assigned treatment. This study is registered with ClinicalTrials.gov, NCT02872116 . Findings: From March 27, 2017, to April 24, 2019, of 2687 patients assessed for eligibility, we concurrently randomly assigned 1581 patients to treatment (nivolumab plus chemotherapy [n=789, 50%] or chemotherapy alone [n=792, 50%]). The median follow-up for OS was 13·1 months (IQR 6·7–19·1) for nivolumab plus chemotherapy and 11·1 months (5·8–16·1) for chemotherapy alone. Nivolumab plus chemotherapy resulted in significant improvements in OS (hazard ratio [HR] 0·71 [98·4% CI 0·59–0·86]; p<0·0001) and PFS (HR 0·68 [98 % CI 0·56–0·81]; p<0·0001) versus chemotherapy alone in patients with a PD-L1 CPS of five or more (minimum follow-up 12·1 months). Additional results showed significant improvement in OS, along with PFS benefit, in patients with a PD-L1 CPS of one or more and all randomly assigned patients. Among all treated patients, 462 (59%) of 782 patients in the nivolumab plus chemotherapy group and 341 (44%) of 767 patients in the chemotherapy alone group had grade 3–4 treatment-related adverse events. The most common any-grade treatment-related adverse events (≥25%) were nausea, diarrhoea, and peripheral neuropathy across both groups. 16 (2%) deaths in the nivolumab plus chemotherapy group and four (1%) deaths in the chemotherapy alone group were considered to be treatment-related. No new safety signals were identified. Interpretation: Nivolumab is the first PD-1 inhibitor to show superior OS, along with PFS benefit and an acceptable safety profile, in combination with chemotherapy versus chemotherapy alone in previously untreated patients with advanced gastric, gastro-oesophageal junction, or oesophageal adenocarcinoma. Nivolumab plus chemotherapy represents a new standard first-line treatment for these patients. Funding: Bristol Myers Squibb, in collaboration with Ono Pharmaceutical.